(untitled) (International Journal of Engineering and Computer Science, 2017)
In backup environments field deduplication yields major advantages. Deduplication is process of automatic elimination of duplicate data in storage system and it is most effective technique to reduce storage costs. De duplication effects predictably in data fragmentation, because logically continuous data is spread across many disk locations. Fragmentation mainly caused by duplicates from previous backups of the same back upset, since such duplicates are frequent due to repeated full backups containing a lot of data which is not changed. Systems with in-line deduplicate intends to detects duplicates during writing and avoids storing them, such fragmentation causes data from the latest backup being scattered across older backups. This survey focused on various techniques to detect inline deduplication. As per literature, need to develop a focused on deduplication reduce the time and storage space. Proposed novel method to avoid the reduction in restores performance without reducing write performance and without affecting deduplication effectiveness.